Valve closure based on pump runaway characteristics in long distance pressurized systems - Xingtao Wang (IWA Publishing, 2021)
In order to guarantee the safety of pumps, valves are installed at the outlet of each pump in long-distance pressurized water supply systems. However, water hammer pressure caused by improper valve closure can tremendously exceed the standard of the pipeline. In this paper, the effects of valve closure on speed of pump and pressure along the pipeline were investigated. Valve closure formula based on pump runaway characteristics were proposed and verified using numerical simulation. In addition, when valves were closed under the formula proposed in this paper and other closure laws, the minimum speed, minimum and maximum pressure along the pipeline were compared. The results showed that formulas agree well with the numerical results. In the high lift supply systems, compared with the other closure laws, the minimum speed and minimum pressure along the pipeline under valve closure formula were the largest, and the maximum pressure along the pipeline was the smallest. Moreover, in the low lift supply systems, the minimum speed under valve closure formula did not exceed the rated speed. Compared with the other closure laws, the minimum pressure along the pipeline was the largest and the maximum pressure along the pipeline was the smallest. HIGHLIGHTS Valve closure formula based on pump runaway characteristics were proposed.; In high lift systems, the minimum speed and minimum pressure along the pipeline under valve closure formula were the largest, and the maximum pressure along the pipeline was the smallest.; In the low lift systems, the minimum speed under valve closure formula did not exceed the rated speed.; Minimum or maximum pressures were the safest.;